IMPLEMENTASI VIRTUAL PRIVATE NETWORK (VPN) DI PERPUSTAKAAN UNIVERSITAS ISLAM MALANG - Umaroh, Lia; Rifauddin, Machsun (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
This study aims to explain to use a VPN in the UNISMA Library. The research method used is descriptive-qualitative and data was obtained through interviews with five informants, observation, and documentation. Data analysis techniques by collecting data, data reduction, data presentation and drawing conclusions. While the validity of the data was obtained through triangulation. The results showed that the use of VPN in the UNISMA Library to speed up internet connection and data privacy. UNISMA library uses a proxy server router operating system for VPN networks. To be able to make Mikrotik a VPN server, configuration is required which includes IP pool configuration, IP router configuration, PPP configuration, DHCP server configuration, NAT by pass firewall configuration and IP security configuration. The library selection of VPN products considers the aspects of strong authentication, encryption that is strong enough, meets standards, integration with other field network services.